Endotoxin and β-1, 3-D-Glucan in Concentrated Ambient Particles Induce Rapid Increase in Blood Pressure in Controlled Human Exposures. Issue 3 (September 2015) - Zhong, Jia; Urch, Bruce; Speck, Mary; Coull, Brent A.; Koutrakis, Petros; Thorne, Peter S.; Scott, James; Liu, Ling; Brook, Robert D.; Behbod, Behrooz; Gibson, Heike; Silverman, Frances; et al.
Abstract : Short-term exposure to particulate matter (PM) is associated with increased blood pressure (BP) in epidemiological studies. Understanding the impact of specific PM components on BP is essential in developing effective risk-reduction strategies. We investigated the association between endotoxin and β-1, 3-D-Glucan—two major biological PM components—and BP. We also examined whether vascular endothelial growth factor, a vasodilatory inflammatory marker, modified these associations. We conducted a single-blind, randomized, crossover trial of controlled human exposure to concentrated ambient particles with 50 healthy adults. Particle-associated-endotoxin and β-1, 3-D-Glucan were sampled using polycarbonate-membrane-filters. Supine resting systolic BP and diastolic BP were measured pre-, 0.5-hour post-, and 20-hour postexposure. Urine vascular endothelial growth factor concentration was determined using enzyme-linked immunosorbant assay and creatinine-corrected. Exposures to endotoxin and β-1, 3-D-Glucan for 130 minutes were associated with increases in BPs: at 0.5-hour postexposure, every doubling in endotoxin concentration was associated with 1.73 mm Hg higher systolic BP (95% confidence interval, 0.28, 3.18; P =0.02) and 2.07 mm Hg higher diastolic BP (95% confidence interval, 0.74, 3.39; P =0.003); every doubling in β-1, 3-D-Glucan concentration was associated with 0.80 mm Hg higher systolic BP (95% confidence interval, −0.07, 1.67; P =0.07) and 0.88 mm Hg higher diastolic BP (95% confidence interval, 0.09, 1.66; P =0.03). Vascular endothelial growth factor rose after concentrated ambient particle endotoxin exposure and attenuated the association between endotoxin and 0.5-hour postexposure diastolic BP ( P interaction =0.02). In healthy adults, short-term endotoxin and β-1, 3-D-Glucan exposures were associated with increased BP. Our findings suggest that the biological PM components contribute to PM-related cardiovascular outcomes, and postexposure vascular endothelial growth factor elevation might be an adaptive response that attenuates these effects.